Mastering system center operations manager 2007 - Price, Brad (Wiley, 2007)
System Center Operations Manager 2007 is designed to make your life easier—and this comprehensive book is your one-stop gateway to it all. With intermediate to advanced coverage, this book gives you the information you need to deploy, manage, and maintain SCOM 2007, and use it to monitor your network.